Interstrip resistance of a semiconductor microstrip detector - Kulibaba, V.; Maslov, N.; Potin, S.; Starodubtsev, A. (Вопросы атомной науки и техники, 2001)
In this work the interelement (interstrip) resistance of the microstrip detector is studied. A few detectors with a different construction are investigated. The dependence of the interstrip resistance on the dose of detector irradiation with electrons is obtained. The possibility of application interstrip resistance measurement for the determination of the good strip yield is shown.